Smoking, telomere length and lung function decline: a longitudinal population-based study. Issue 3 (19th July 2017) - Andujar, Pascal; Courbon, Dominique; Bizard, Emilie; Marcos, Elisabeth; Adnot, Serge; Boyer, Laurent; Demoly, Pascal; Jarvis, Debbie; Neukirch, Catherine; Pin, Isabelle; Thabut, Gabriel; Boczkowski, Jorge; et al.
Abstract : Telomere shortening is associated with COPD and impaired lung function in cross-sectional studies, but there is no longitudinal study. We used data from 448 participants recruited as part of the French follow-up of the European Community Respiratory Health Survey. We found no relationship between telomere length at baseline and FEV1 decline after 11 years of follow-up. However, heavy smoking was associated with an accelerated FEV1 decline in individuals with short telomeres, but not in subjects with longer telomeres (p for interaction p=0.08). Our findings suggest that short telomere length in peripheral leucocytes might be a marker for increased susceptibility to the effect of smoking.